Anthelmintic activity of plants against gastrointestinal nematodes of goats: a review. Issue 10 (14th June 2019) - Oliveira Santos, Francianne; Ponce Morais Cerqueira, Amanda; Branco, Alexsandro; José Moreira Batatinha, Maria; Borges Botura, Mariana
Abstract: The gastrointestinal nematodes (GIN) stand out as an important cause of disease in small ruminant, especially on goat farm. Widespread resistance to synthetic anthelminthics has stimulated the research for alternative strategies of parasite control, including the use of medicinal plants. The present work summarizes the in vitro and in vivo studies of plants with activity against GIN of goats, focusing on the description of chemical constituents related to this effect. This review retrieved 56 scientific articles from 2008 to 2018 describing more than 100 different plant species. The most frequently investigated family was Fabaceae (30.7%). Most in vitro studies on the activity of plant extracts and fractions were carried out with of free-living stages nematodes. In vivo studies were conducted mainly with the use of plants in animal feed and generally showed lower effectiveness compared to in vitro assays. The main plant secondary metabolites associated with anthelmintic effect are condensed tannins, saponin and flavonoids. However, the studies with compounds isolated from plants and elucidation of their mechanisms of action are scarce. Herbal medicines are thought to be promising sources for the development of effective anthelmintic agents.